Studi Perilaku Konsumen dalam Memanfaatkan Fitur Live Shopping di Platform Shopee - Mhd Raafi Abrar Azzuri; Lyvia Zahra Khalida; Silva Arrum; M Ikhsan; Safrizal Putra; Ikhah Malikhah (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze consumer behavior in utilizing the live shopping feature on the Shopee platform. The live shopping feature is an innovation in e-commerce that combines direct interaction between sellers and buyers in real time, thus influencing consumer purchase intention and decision-making. The research method used was qualitative through interviews with 10 management students with a concentration in digital business who use the live shopping feature. Data was obtained through in-depth interviews and observations of students actively using the live shopping feature on Shopee. The results indicate that ease of use, direct interaction with sellers, promotions during live broadcasts, and trust in the product are the most influential factors in shaping consumer behavior. Furthermore, live shopping is considered capable of creating a more interactive, enjoyable, and convincing shopping experience, thereby increasing purchase intention. This research is expected to contribute to online businesses in designing more effective digital marketing strategies through the utilization of the live shopping feature, taking into account aspects of the experience and direct consumer interaction.